The narrative of social (in)justice, feminism, and migration in Slavenka Drakulić's selected works - Flis, Leonora (Dve domovini, 2023)
Slavenka Drakulić (1949) is a renowned Croatian journalist and writer who started her professional career in Croatia but later gained popularity in other European countries and the United States, where many of her books were published. Her writing has been marked by social criticism and feminist traits. The article focuses on her works that point to questions of social (in)equality and the marginalization of certain social groups or even nations. Moreover, her works expose the position of women in society and shed light on migrations, whether through the images of refugees from crisis zones or migrations from Eastern Europe to the West for political and economic reasons.
Keywords: Croatian literature; Croatian women writers; Drakulić, Slavenka; Družbena neenakost; Družbena obrobnost; feminism; Feminizem; Hrvaška književnost; Hrvaške pisateljice; Izseljevanje in priseljevanje; Literarne študije; marginalization; migration; social inequality